Perinatal outcomes and predictors of neonatal mortality in preterm premature rupture of membranes: a tertiary center experience - Recep Taha Ağaoğlu; Özge Öztürk; Can Ozan Ulusoy; Figen Günday; Dilara Sarikaya Kurt; Meltem Aksu; Burak Hizli; Kadriye Yakut Yücel (BMC Pregnancy and Childbirth)
Abstract Background Preterm premature rupture of membranes (PPROM) is a serious obstetric condition associated with increased maternal, fetal, and neonatal morbidity and mortality. It accounts for approximately one-third of all spontaneous preterm births and is associated with complications such as respiratory distress syndrome (RDS), sepsis, pulmonary hypoplasia, and neonatal mortality. Despite significant advances in prenatal care, proper management, particularly in early gestational age, remains unclear. Identifying factors associated with neonatal mortality in PPROM is important to develop therapeutic interventions and improve perinatal outcomes. Methods This retrospective study examined clinical data and neonatal outcomes in 183 pregnant women with PPROM between the gestational ages of 23 and 36 + 6 weeks who were admitted to a tertiary referral hospital. The study population was categorized into four gestational age cohorts: Group I (23–27 + 6 weeks), Group II (28–31 + 6 weeks), Group III (32–33 + 6 weeks), and Group IV (34–36 + 6 weeks). Neonatal outcomes, including admission to the neonatal intensive care unit (NICU), the incidence of respiratory distress syndrome, the requirement for oxygen and mechanical ventilation, the necessity for surfactant and inotropic support, sepsis, suspected pulmonary hypoplasia, and early and late neonatal mortality were compared between the groups. Results Group I had the highest CRP values (18.68 ± 21.34), while Group III had the lowest (6.81 ± 5.16). Significant differences were found between the groups in terms of death at discharge, gestational age at delivery, birth weight, and presence of oligohydramnios. The intubated group had higher CRP levels and lower gestational age and birth weight. Of the 14 neonatal deaths, eight occurred in the early neonatal period, corresponding to a mortality rate of 7.6%. The neonatal mortality rate was 63.2% in Group I. No deaths were recorded in Groups II and III. In Group IV, the mortality rate was 2.2%. Conclusion Neonatal mortality was associated with low gestational age, low birth weight, and oligohydramnios. The predominant cause of early infant deaths was RDS, whereas late neonatal mortality was primarily attributed to sepsis. Specifically, active management options after 34 weeks of gestational age have demonstrated enhancements in neonatal outcomes, underscoring the significance of tailored clinical approaches in cases of PPROM.